Enhancing Phenolic Maturity of Syrah with the Application of a New Foliar Spray - Villangó, Sz.; Pásti, Gy.; Kállay, M.; Leskó, A.; Balga, I.; Donkó, A.; Ladányi, M.; Pálfi, Z.; Zsófi, Zs. (South African Journal of Enology and Viticulture, 2016)
Climate change is inducing earlier grape ripening, especially in warm vintages. This phenomenon is resulting in unbalanced wines an alcohol concentration that is too high and titratable acidity that is low, along with a high pH level without the desired level of phenolic maturity. Final wine quality notably depends on the phenolic composition of the grapes and the extractability of these compounds. This research was designed to test a new foliar spray, called LalVigne® MATURE, for its capacity to create a balance between sugar development and phenolic maturity. It is a formulation of 100% natural, inactivated wine yeast derivatives. This foliar spray was tested on Syrah vines in two vintages (2012 and 2013) in a cool-climate wine region (Eger, Hungary). The spray acted as an elicitor, stimulating the synthesis of several secondary metabolites. The changes in anthocyanin extractability and texture characteristics of the grape berries were followed during ripening. Experimental wines were made at three separate harvest times in each vintage. Standard analytical parameters were evaluated for grapes and wines, as well as for resveratrol. Grapes from the treated vines had thicker skins than the controls at all sampling dates in both vintages. The phenolic potential (especially anthocyanin concentration and extractability) of the foliar spray-treated grapes was greatly improved. Our experiment showed that phenolic ripening can be enhanced using the foliar spray, and that its application was useful in different vintages.